The role of corepressor HOS15-mediated epigenetic regulation of flowering - Huang, Li-Jun; Wang, Yukun; Lin, Zeng; Jiang, Dong; Luo, Yong; Li, Ning (Frontiers in Plant Science, 2023)
Regulation of gene expression underpins gene function and is essential for regulation of physiological roles. Epigenetic modifications regulate gene transcription by physically facilitating relaxation or condensation of target loci in chromatin. Transcriptional corepressors are involved in chromatin remodeling and regulate gene expression by establishing repressive complexes. Genetic and biochemical studies reveal that a member of the Groucho/Thymidine uptake 1 (Gro/Tup1) corepressor family, HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENE 15 (HOS15), is recruited via the evening complex (EC) to the GIGANTEA (GI) promoter to repress gene expression, and modulating flower development. Therefore, HOS15 connects photoperiodic pathway and epigenetic mechanism to control flower development in plants. In addition, growing body of evidence support a diverse roles of the epigenetic regulator HOS15 in fine-tuning plant development and growth by integrating intrinsic genetic components and various environmental signals.